1989
DOI: 10.2307/1956437
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Affairs and Issue Voting: Do Presidential Candidates “Waltz Before a Blind Audience?”

Abstract: hile candidates regularly spend much time and effort campaigning on foreign and defense policies, the thrust of prevailing scholarly opinion is that voters possess little information and weak attitudes on these issues, which therefore have negligible impact on their voting behavior. We resolve this anomaly by arguing that public attitudes on foreign and defense policies are available and cognitively accessible, that the public has perceived clear differences between the candidates on these issues in recent ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
227
0
5

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(240 citation statements)
references
References 25 publications
4
227
0
5
Order By: Relevance
“…The authors stress the relevance of scholars casting their attention not just on the familiar forms of trust, but on other forms as well. Political scientists have also shown that public opinion about world affairs can influence voting behavior and public policy (Aldrich et al 1989 andShapiro andJacobs 2000). To measure international trust Brewer et al (2004Brewer et al ( , 2005 use the following questions: Generally speaking, would you say that the United States can trust other nations, or that the United States can't be too careful in dealing with other nations?…”
Section: Introductionmentioning
confidence: 99%
“…The authors stress the relevance of scholars casting their attention not just on the familiar forms of trust, but on other forms as well. Political scientists have also shown that public opinion about world affairs can influence voting behavior and public policy (Aldrich et al 1989 andShapiro andJacobs 2000). To measure international trust Brewer et al (2004Brewer et al ( , 2005 use the following questions: Generally speaking, would you say that the United States can trust other nations, or that the United States can't be too careful in dealing with other nations?…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, that has been the prevailing view in political science. Aldrich, Sullivan, and Borgida (1989), however, find that voters are paying attention to foreign affairs and voting on them when the candidates show substantial differences. Also, note that Fiorina (1981b) found that voters are paying some attention to foreign affairs when voting.…”
Section: Notesmentioning
confidence: 98%
“…A second reason suggesting the plausibility that policy updating occurs is found in cross-sectional studies of presidential evaluations and voting behavior. When policy preferences are included in these models, nontrivial effects are often reported (Newman 2003;Abramowitz 1995;Aldrich et al 1989;Miller and Shanks 1996;Ansolabehere et al 2008;Goren 2002). While this does not automatically imply that policy attitudes influence how people revise their presidential assessments, it certainly raises the possibility.…”
Section: Policy Attitudes and Presidential Evaluationsmentioning
confidence: 99%